The use of that-clauses in abstracts written by Brazilian research-students - Lopes Alves, Anna Luisa [UNESP]; Pinto, Paula Tavares [UNESP] (Federal Univ Ceara, 2018)
The writing of abstracts has been studied by researchers from different areas (BATHIA, 1993; SWALES; FEAK, 2009;) so that it is possible to observe which standards are most used by authors of international impact journals in order to prepare researchers for the writing of this textual genre. In this paper, we aim to demonstrate, through corpus analysis, how that-clauses are used in academic abstracts productions of English learners, specifically when they write about their findings, results, and research conclusion (rhetorical moves 4 and 5 of Swales and Feak (2009)). In addition, we have based our work on a theory that permeates Corpus Linguistics (LC), focused on teaching and learning English for Academic Purposes (EAP). After collecting and compiling our corpus, we used the computer program Sketch Engine (KILGARRIFF et al, 2014) to generate concordance lines with the word that and, based on the results, we observed that in the writing of the learners, the structures most used to report the findings, results and conclusions of research were: subject + simple past + that, and subject + present simple + that, aligning with research results of authors such as Biber et al. (2007) and Glasman-Deal (2010). The final result showed that it is possible to use the LC for EAP teaching and learning and also for the development of didactic activities and to obtain a positive result. To conclude, we can say that LC is a comprehensive area that allows several types of applications for analysis of linguistic data for the most diverse purposes.
Keywords: Corpus Linguistics and teaching; Abstracts; That-clauses